Identifikasi Profil Sensori Ideal Minuman Fermentasi Kulit Buah Nanas (Ananas comosus L.): Ideal Sensory Profile Identification of Fermented Drinks Based on Pineapple Peel (Ananas comosus L.) - Pratiwi, Caca; Saufani, Iza Ayu; Nurfaziah, Latifah Rahman (Universitas Airlangga, 2024)
Background: The inedible parts of pineapple account for 40% of its weight, including the peel, which can be utilized through fermentation into a beverage known as tepache. This probiotic drink holds significant potential for industrial development in Indonesia. However, there is limited information regarding the sensory profiles and consumer preferences specific to the Indonesian market. Objectives: This study aimed to analyze the ideal sensory profile of fermented beverages made from pineapple peel. Methods: This experimental study consisted of three stages: product formulation, sensory evaluation using the ideal profile method, and sensory evaluation using Quantitative Descriptive Analysis (QDA). A completely randomized design (CRD) with a single-factor approach was used, involving three treatments: sample A (500 g pineapple peel and 500 g palm sugar), sample B (500 g pineapple peel and 600 g palm sugar), and sample C (500 g pineapple peel and 700 g palm sugar). Each treatment was replicated twice. Data on sensory profiles were processed using Microsoft Excel. Results: The sensory profile of product code A most closely resembled the ideal profile, particularly with the peely attribute. The attributes requiring a decrease in intensity for product code A were rich, citric, bitter, astringent, and acidic. Conversely, the attributes needing an increase were light, sparkle, sweet, and fresh Conclusions: Consumer perceptions indicate that the product with sensory characteristics closest to the ideal profile is product code A.